Pengaruh BI Rate, Tingkat Inflasi, dan Harga Emas terhadap Penyaluran Pembiayaan Gadai Emas di Bank Umum Syariah Indonesia - Dhiya Azkia Dirgantari; Benny Barnas; Kristianingsih Kristianingsih (Journal of Applied Islamic Economics and Finance, 2022)
This study was conducted to analyze external factors of Sharia banks that are suspected to have an influence on the distribution of gold pawn financing namely the BI Rate, inflation rate and gold price. This research use gold pawn product of Bank BRI Syariah for the object research, there is Qardh Beragun Emas period 2015-2020. Data analysis is descriptive quantitative analysis with analysis technique use multiple linear regression method, hypothesis testing and classical assumption test. The result of this study indicate that BI Rate have no significant effect, Inflation Rate has a significant positive effect on gold pawn financing, Gold price has significant positive effect on gold pawn financing, and simultaneously BI Rate, inflation rate and gold pricehave significant effect on gold pawn financing.